The Effect of Mind Mapping Technique Towards the Students’ Speaking Ability At 7th Grade of SMPN 4 Bandar Lampung - Frederika Mei Anggraeni (International Conference on Education and Language (ICEL), 2014)
The main objective of this research was aimed to identify whether the use of Mind Mapping technique was effective in improving the students’ speaking achievement. The population was the First year students of SMPN 4 Bandar Lampung in academic year of 2013/2014 with a total number of 234 students. Out of this population, 52 students were taken as sample. There were two groups, each of which consisted of 26 students. One class became the experimental, while the other one became the control group. Different treatments were given to both groups, that was mind mapping given to the experimental group while the control group taught by traditional teaching. The test of speaking was the instrument and then administered in two sections: pretest and posttest. The score obtained was analyzed by using t-test formula. The experimental data revealed two important results. First, adopting a technique of mind mapping technique could significantly improve the students’ speaking ability because itwas supported by pictures and colors. Results were obtained of experimental groups revealed that mind mapping performed better on the post test. Second, the final findings of this research were formulated. Fromthet-testcalculationofthepretest of experimental group the resultwas1856.4 and the post-test was 5644.82 with the achievement until 19.5%. Whereas in control group the result of pretest was 1856.6 and the post test was 1952.3 with the achievement 4.9%. The result of this study showed that the students taught by mind mapping technique got better score than those who were not. It could be seen that the students’ speaking ability in the experimental group after treatment was significant. By calculating the scores to the t-Test, the result was Pvalue 1% = 2,68,Pvalue 5% = 2,01. Moreover, the t-Test value was 7,6. It described clearly that the t-Test value was greater than the p value. This meant that the application of mind mapping technique was very effective technique. Therefore, it could be concluded that Mind Mapping Technique improved the students’ speakingachievement.